Tobacco use and cessation counseling in India-data from the Global Health Professions Students Survey, 2005-09 - Surani, N; Pednekar, M; Sinha, D; Singh, G; Warren, C; Asma, S; Gupta, P; Singh, P (Indian journal of cancer, 2012)
Context: Tobacco use by health professionals reflects the failure of healthcare systems in protecting not only beneficiaries of the system but also those involved in health care delivery. Aim: The aim of this study was to report findings from the Global Health Professions Students Survey (GHPSS) conducted in medical, dental, nursing and pharmacy schools in India. Settings and Design: A cross-sectional survey was conducted in Indian dental and medical schools (in 2009), nursing (in 2007), and pharmacy (in 2008) schools. Materials and Methods: Anonymous, self-administered GHPSS questionnaire covering demographics, tobacco use prevalence, secondhand smoke (SHS) exposure, desire to quit smoking and training received to provide cessation counseling to patients was used. Statistical Analysis: Proportions and prevalence were computed using SUDAAN and SPSS 15.0. Results: Current cigarette smoking and other tobacco use ranged from 3.4-13.4% and 4.5-11.6% respectively, in the four health professional schools, with the highest numbers for medical schools and males. Enforcement of smoking ban in medical schools was low (53%) compared to nursing (86.4%), pharmacy (85.5%), and dental (90.8%) schools. Ninety percent students thought health professionals have a role in giving smoking cessation advice to their patients. Three out of five current smokers wanted to quit. However, one out of two reported receiving help/advice to quit. Although all expressed the need, 29.1-54.8% students received cessation training in their schools. Conclusion: Tobacco control policy, cessation training and initiatives to help students quit smoking should be undertaken.